PENGARUH BADAN USAHA MILIK DESA (BUMDes) TERHADAP KOPERASI UNIT DESA (KUD) DI INDONESIA, EFEK CROWDING IN ATAU CROWDING OUT? - Gabetini, Grace; Qibthiyyah, Riatu Mariatul (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.14.NO.03.TAHUN.2025, 2025)
This study aims to analyze the impact of establishing Village-Owned Enterprises (BUMDes) on the existence of Village Unit Cooperatives (KUD) in Indonesia. In the context of rural economic development, BUMDes are expected to empower rural communities and enhance economic self-reliance. However, the presence of BUMDes also creates competition for pre-existing business entities in villages, particularly KUD, which have long served as a cornerstone of rural economies. This research employs a quantitative approach with fixed-effect panel data regression analysis, integrating secondary data from the Central Bureau of Statistics, the Ministry of Villages, Development of Disadvantaged Regions, and Transmigration, the Ministry of Home Affairs, and the Ministry of Finance for the period of 2014 to 2021. The results of the study indicate that the establishment of BUMDes has the potential to create a crowding-in effect for KUD through healthy competition that promotes the continued presence of KUD in Indonesia. These findings provide valuable insights for the development of more effective and sustainable rural economic policies, as well as encouraging collaboration between BUMDes and KUD to address the complex economic challenges at the village level.